Deteksi Lapisan Bawah Permukaan di Desa Wajok Hilir Menggunakan Metode Geolistrik Resistivitas Konfigurasi Wenner-Schlumberger - Aisyah Rafa; Zulfian Zulfian; Radhitya Perdhana; Joko Sampurno; Irfana Diah Faryuni (BULETIN FISIKA, 2026)
Research on the detection of subsurface layers using the Wenner-Schlumberger resistivity geoelectrical method was conducted in Wajok Hilir Village, Mempawah Regency, West Kalimantan Province. This research employed a Geotitis GL-MD-300 resistivity meter. The survey was conducted along three lines, each 260 m in length, using the geoelectrical method. Based on the two dimensional modeling results, the three lines exhibit resistivity values ranging from 5.69 to 3890 Ωm, and interpreted as three subsurface layers: a clay layer at depths of approximately 2,5 until 18.5 m with resistivity values of 5,69 until 237 Ωm, a sandy clay layer at depths of 2.5 until 24.9 m with resistivity values of 237 until 1531 Ωm, and a sand layer extending to depths of up to 39.6 m with resistivity values of 1531 until 3890 Ωm. This information on subsurface layers can be used as supporting data for development planning, environmental management, and hazard mitigation in the region.